Cerebral toxoplasmosis in a diffuse large B cell lymphoma patient - Savšek, Lina (Radiology and oncology (Ljubljana), 2016)
Toxoplasmosis is an opportunistic protozoal infection that has, until now, probably been an underestimated cause of encephalitis in patients with hematological malignancies, independent of stem cell or bone marrow transplant. T and B cell depleting regimens are probably an important risk factor for reactivation of a latent toxoplasma infection in these patients. Case report. We describe a 62-year-old HIV-negative right-handed Caucasian female with systemic diffuse large B cell lymphoma who presented with sudden onset of high fever, headache, altered mental status, ataxia and findings of pancytopenia, a few days after receiving her final, 8th cycle of rituximab, cyclophosphamide, vincristine, doxorubicin, prednisolone (R-CHOP) chemotherapy regimen. A progression of lymphoma to the central nervous system was suspected. MRI of the head revealed multiple on T2 and fluid attenuated inversion recovery (FLAIR) hyperintense parenchymal lesions with mild surrounding edema, located in both cerebral and cerebellar hemispheres that demonstrated moderate gadolinium enhancement. The polymerase chain reaction on cerebrospinal fluid (CSF PCR) was positive for Toxoplasma gondii. The patient was diagnosed with toxoplasmic encephalitis and successfully treated with sulfadiazine, pyrimethamine and folic acid. Due to the need for maintenance therapy with rituximab for lymphoma remission, the patient now continues with secondary prophylaxis of toxoplasmosis. Conclusions. With this case report, we wish to emphasize the need to consider cerebral toxoplasmosis in patients with hematological malignancies on immunosuppressive therapy when presenting with new neurologic deficits. In such patients, there are numerous differential diagnoses for cerebral toxoplasmosis, and the CNS lymphoma is the most difficult among all to distinguish it from. If left untreated, cerebral toxoplasmosis has a high mortality rate; therefore early recognition and treatment are of essential importance.
Keywords: cerebral; limfomi; lymphoma; osrednje živčevje; rituksimab; rituximab; toksoplazmoza; toxoplasmosis